Accelerating Sexual Violence Response Through Digital Innovations: An Evaluation of the LONTARA Platform in Makassar - Nediya Syafitri Hasanuddin; Muhlis Madani; Ihyani Malik; Nuryanti Mustari (Lembaga Bale Literasi, 2026)
This study analyzes the digital platform-based service innovation through the Lontara application in handling sexual violence in Makassar City. Utilizing a qualitative-descriptive research design, data were collected through in-depth interviews, non-participant observations, and documentation. The informants consisted of nine key actors, including the Integrated Service Unit for the Protection of Women and Children (UPTD PPA) officers, the Women and Children Protection Unit of the Polrestabes Makassar (PPA Police), and survivors of sexual violence. Grounded in Everett M. Rogers’ Diffusion of Innovations theory, the study evaluates five core attributes: relative advantage, compatibility, complexity, trialability, and observability. The findings reveal that while the Lontara platform significantly enhances early reporting accessibility, shortens administrative response times, and facilitates initial multi-sectoral coordination, its field execution faces several strategic barriers. These hurdles include substantial digital literacy gaps among vulnerable socio-economic groups, technical connectivity issues in suburban districts, and persisting cultural taboos that reinforce underreporting due to fear of social stigma. Furthermore, systemic integration between the municipality's digital platform and the police force’s judicial database remains loosely coupled. This research recommends comprehensive public socialization, UI/UX simplification, enhanced end-to-end data encryption to protect survivor anonymity, and the institutionalization of standardized digital-to-judicial referral protocols to optimize protection and recovery outcomes.